FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Yohana Ernawati; Lilis Ardini (STIE PGRI Dewantara Jombang, 2022)
In the situation of economic growth and development in Indonesia which has a very rapid impact on competition. Competition has become tighter felt by various companies, namely trading companies, service companies, and manufacturing companies which have the same goal, namely to be able to earn and increase profits by taking into account the existing market share in order to maintain viability. The research was conducted to determine the factors that have a significant effect on the acceptance of a going concern audit opinion. The factors that can influence the acceptance of going concern audit opinions include, namely, KAP reputation, company size, and the previous year's audit opinion. The research method used is a qualitative descriptive method in the form of a literature review/study of the literature, that is, the results of the research are explained in one sentence. The results of the analysis show that financial factors have a more significant influence in obtaining acceptance of a going concern audit opinion.